Biorefineries : an introduction - Aresta, Michele, 1940-; Dibenedetto, Angela; Dumeignil, Franck (De Gruyter graduate., 2015)
Replacing fossil fuels with renewable resources is a major challenge these days. This book presents the basic science and technologies used to convert terrestrial and aquatic biomass into fuels and chemicals. The value chain for biomass conversion into platform molecules and their transformation into final products are presented in detail. Focusing on both general sciences and innovations in the field, this book is intended for students and researchers in industry.